POLYPLOIDY: EVOLUTIONARY ADAPTABILITY, AGRICULTURAL PROSPECTS, AND PRESSING CHALLENGES (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Polyploidy is a genetic phenomenon characterized by the presence of more than two sets of chromosomes in an organism's cells, beyond the diploid state, playing a significant role in evolutionary processes. This article examines the positive aspects of polyploidy, particularly the increase in genetic diversity, stress resistance, the emergence of new species, and increased productivity in agriculture. Furthermore, the article analyzes the pressing challenges associated with polyploidy, among which genetic instability and reduced fertility are particularly noteworthy. The article offers suggestions on how to address these challenges and utilize polyploidy more effectively. The research concludes by assessing its impact on agriculture and evolutionary biology and outlining directions for future research.